(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The role of international legal standards in the legalization (money laundering) of income from criminal activity, the main features of this type of crime and the scope of amaï cases aimed at its prevention are threatened. As we know, legalization of income from criminal activity is a type of secondary crime, and we can not imagine this type of crime without offshore ways. In this course of study, various approaches to the definition of the concept of legalization of proceeds from crime analyzed. The collaboration between governments, financial institutions, and international organizations in combating illegal financial activities is explored, emphasizing the escalating significance of stringent controls.